SPOTLIGHT on a visit to the Rand Refinery - David J. Haddock (The Southern African Institute of Mining and Metallurgy, 1988)
On Wednesday, 6th July, 1988, 28 members of the Johannesburg Branch of The South African Institute of Mining and Metallurgy and their guests assembled at the Rand Refinery Sports Club, which is situated within the Refinery complex, to hear Dr Daniel Polnow, General Manager of the Refinery, give a very interesting lecture on the Rand Refinery Complex and its activities. Accounting for gold The South African Institute of Mining and Metallurgy will be holding a 3- or 4-day school in the third week of May 1989 on the topic 'Accounting for Gold'.